Aramaic sources of Mark's Gospel - Casey, Maurice (Monograph series (Society for New Testament Studies), 1998)
This book goes behind the Greek text of the Gospel of Mark and reconstructs some of its sources in the original Aramaic, the language which Jesus spoke. This work has been made possible by the publication of all the Aramaic Dead Sea Scrolls, which provide a basis of Jewish Aramaic for the right period.